Opportunities and Obstacles for Citizen Science : Insights from Finnish Public Libraries - Svahn, Elena; Andersdotter, Karolina; Kallio, Miki (Nordic Journal of Library and Information Studies, 2025)
The primary aim of this study was to gain understanding on public library perspectives on citizen science in Finland, through examining the conditions of public libraries in three key areas: physical space, digital space, and knowledge resources and infrastructure. Additionally, the study sought to explore how libraries conceptualise an environment supportive for citizen science. In April 2024, an online survey was conducted with 55 public library representatives from Finland, gathering data on their views about public libraries’ capability to support citizen science. The survey included a series of questions focusing on the three aforementioned areas. The responses were analysed using thematic analysis. Eleven key concepts supporting citizen science in public libraries were identified: inclusivity and accessibility to diverse communities, meeting and event spaces, study and work areas, role of libraries as connectors, collaboration with educational institutions, national cooperation, community engagement and events, customer service, local collections and research, technology and digital resources, and library staff. Librarians perceived libraries as facilitators rather than leaders of citizen science projects, emphasising the importance of collaboration and accessibility of resources. The results show the potential of Finnish public libraries to facilitate citizen science, simultaneously revealing challenges related to infrastructure, resources, and role delineation. Findings confirm the potential of Finnish public libraries to support citizen science initiatives while highlighting areas for improvement. These insights may be useful in designing effective strategies for integrating citizen science into library services, thus responding to an important research, programmatic, and policy gap.